Aplicación de estrategias de lectura de icono verbales en la comprensión lectora en los niños de cinco años de la institución educativa inicial N° 6010375 27 de Octubre, Ramón Castilla 2024 - Gonzales Carihuasari, Karina (2025)
The purpose of this research is to determine the effects of the application of verbal icon reading strategies on reading comprehension in five-year-old children at the Early Childhood Education Institution N°6010375, 27 of October, Ramón Castilla 2024. The research is quantitative in nature, using an experimental design with two groups: control and experimental. The study population consists of all five-year-old children at the Early Childhood Education Institution N°6010375, 27 of October, Ramón Castilla 2024, totaling 69 boys and girls. Observation and an observation guide were used as the technique and instrument for data collection, which were subjected to validity and reliability testing prior to application. These were evaluated by three experts in the field, and reliability was assessed using Cronbach's Alpha coefficient. After a pilot test, a value of 0.836 was obtained. The results showed a p-value = 0.000 < α = 0.01, leading to the rejection of Ho and acceptance of Ha at a 1% significance level. It was concluded that the application of the strategy has significant effects on reading comprehension in children at the Early Childhood Education Institution N°6010375.